2014
DOI: 10.4048/jbc.2014.17.3.226
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Risk Assessment Models for Predicting the Incidence of Breast Cancer in Korean Women

Abstract: PurposeThe Gail model is one of the most widely used tools to assess the risk of breast cancer. However, it is known to overestimate breast cancer risk for Asian women. Here, we validate the Gail model and the Korean model using Korean data, and subsequently update and revalidate the Korean model using recent data.MethodsWe validated the modified Gail model (model 2), Asian American Gail model, and a previous Korean model using screening patient data collected between January 1999 and July 2004. The occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 15 publications
1
23
2
1
Order By: Relevance
“…The Gail model might overestimate the risk of and development of breast cancer in other populations in which other races predominate (Novotny et al, 2006;Andreeva and Pokhrel 2013;Wang et al, 2018). However, utilization of the Gail model for Turkish population and other populations with white women predominance might provide more accurate estimations (Tice et al, 2005;Min et al, 2014;Wang et al, 2018). Accordingly, the five-year and life-time estimated risk for breast cancer was not higher in our study than different studies (Tice et al, 2005;Min et al, 2014;Khazaee-Pool et al, 2016, Wang et al, 2018.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The Gail model might overestimate the risk of and development of breast cancer in other populations in which other races predominate (Novotny et al, 2006;Andreeva and Pokhrel 2013;Wang et al, 2018). However, utilization of the Gail model for Turkish population and other populations with white women predominance might provide more accurate estimations (Tice et al, 2005;Min et al, 2014;Wang et al, 2018). Accordingly, the five-year and life-time estimated risk for breast cancer was not higher in our study than different studies (Tice et al, 2005;Min et al, 2014;Khazaee-Pool et al, 2016, Wang et al, 2018.…”
Section: Discussioncontrasting
confidence: 67%
“…However, utilization of the Gail model for Turkish population and other populations with white women predominance might provide more accurate estimations (Tice et al, 2005;Min et al, 2014;Wang et al, 2018). Accordingly, the five-year and life-time estimated risk for breast cancer was not higher in our study than different studies (Tice et al, 2005;Min et al, 2014;Khazaee-Pool et al, 2016, Wang et al, 2018. Unfortunately, the Gail model for breast cancer risk prediction of consanguineous marriages for fist degree and second-degree relatives is not included as a risk factor.…”
Section: Discussioncontrasting
confidence: 63%
“…The Gail model was used widely since then but it is known to overestimate breast cancer risk for Asian women [5]. The updated Korean model proposed by Min et al in 2014 [6], including risk factors of age, body mass index, menopause status, breast feeding, family history, previous breast test and age at first delivery, showed a better performance than the other models for Asian women.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Korean study showed a 50% underestimation of breast cancer risk among Korean women based on the modified Korean risk model developed using risk factors from a Korean case-control study and the incidence and mortality in Korea. For a more accurate prediction model, clinical information may not be adequate; biochemical data, such as estrogen level, mammographic density and molecular markers may need to be included to assure great discriminatory power [19].…”
Section: Discussionmentioning
confidence: 99%
“…The Gail Model has been widely used to assess women's risk of getting breast cancer; nevertheless, data using this model on women outside of Europe and North America are limited. The modified Gail score that was tailored to women of Asian descent as well as risk predictions scores were developed for Singapore and Korean women [16][17][18][19] while the application of Gail model in China is relatively scarce.…”
Section: Introductionmentioning
confidence: 99%